The functional decline of tomato plants infected by Candidatus Liberbacter solanacearum: an RNA-seq transcriptomic analysis - Chuan, Jiacheng; Nie, Jingbai; Cooper, William Rodney; Chen, Wen; Hale, Lawrence; Li, Xiang (Frontiers in Plant Science, 2024)
Candidatus Liberibacter solanacearum (CLso) is a regulated plant pathogen in European and some Asian countries, associated with severe diseases in economically important Apiaceous and Solanaceous crops, including potato, tomato, and carrot. Eleven haplotypes of CLso have been identified based on the difference in rRNA and conserved genes and host and pathogenicity. Although it is pathogenic to a wide range of plants, the mechanisms of plant response and functional decline of host plants are not well defined. This study aims to describe the underlying mechanism of the functional decline of tomato plants infected by CLso by analyzing the transcriptomic response of tomato plants to CLso haplotypes A and B. Next-generation sequencing (NGS) data were generated from total RNA of tomato plants infected by CLso haplotypes A and B, and uninfected tomato plants, while qPCR analysis was used to validate the in-silico expression analysis. Gene Ontology and KEGG pathways were enriched using differentially expressed genes. Plants infected with CLso haplotype B saw 229 genes upregulated when compared to uninfected plants, while 1,135 were downregulated. Healthy tomato plants and plants infected by haplotype A had similar expression levels, which is consistent with the fact that CLso haplotype A does not show apparent symptoms in tomato plants. Photosynthesis and starch biosynthesis were impaired while starch amylolysis was promoted in plants infected by CLso haplotype B compared with uninfected plants. The changes in pathway gene expression suggest that carbohydrate consumption in infected plants was more extensive than accumulation. In addition, cell-wall-related genes, including steroid biosynthesis pathways, were downregulated in plants infected with CLso haplotype B suggesting a reduction in membrane fluidity, cell signaling, and defense against bacteria. In addition, genes in phenylpropanoid metabolism and DNA replication were generally suppressed by CLso infection, affecting plant growth and defense. This study provides insights into plants' defense and functional decline due to pathogenic CLso using whole transcriptome sequencing and qPCR validation. Our results show how tomato plants react in metabolic pathways during the deterioration caused by pathogenic CLso.